Risks of Sulpiride-Induced Parkinsonism in Peptic Ulcer and Gastroesophageal Reflux Disease Patients in Taiwan: A Nationwide Population-Based Study - Wei, Cheng-Yu; Tzeng, I-Shiang; Lin, Mei-Chen; Yeh, Yung-Hsiang; Hsu, Chung Y.; Kung, Woon-Man (Frontiers in Pharmacology, 2020)
Background: Sulpiride is a highly selective dopamine D2 receptor antagonist and is commonly used in psychiatric disorders, Tourette syndrome, peptic ulcer disease (PUD), and gastroesophageal reflux disease (GERD). However, sulpiride has been recognized as a potential cause of drug-induced parkinsonism (DIP) for a long time. In this study, we aimed to focus on analysis of sulpiride-induced parkinsonism (SIP) in PUD and GERD patients based on a nationwide population. Methods: Data were obtained from the Taiwan’s National Health Insurance Research Database. The study enrolled 5,275 PUD or GERD patients, of whom were divided into two groups, based on their exposure (1,055 cases) or non-exposure (4,220 cases) to sulpiride. Results: During the study period (2000–2012), the incidence rate of parkinsonism was 261.5 and 762.2 per 100,000 person-years in the control and sulpiride-treated groups, respectively. For patients with at least 14 days of prescription for sulpiride, the adjusted hazard ratio (aHR) was 2.89, 95% confidence interval (CI): 2.04-4.11. Patients with age more than 65 years (aHR = 4.99, 95% CI = 2.58-9.65), hypertension (aHR = 2.39, 95% CI = 1.49-3.82), depression (aHR = 2.00, 95% CI = 1.38-2.91), and anxiety (aHR = 1.45, 95% CI = 1.01-2.09) had significant higher risk of developing parkinsonism. An average annual cumulative sulpiride dose > 1,103 mg was accompanied by the greatest risk of SIP; sulpiride use for  9 days is a cut-off point for predicting future SIP. Conclusion: At the population level, sulpiride may be frequently prescribed and apparently effective for PUD and GERD. SIP is associated with older age, hypertension, depression or anxiety comorbidities. Physicians should be aware of the neurogenic adverse effects, even when the drug is only used in low-dose or a short duration.